Are simple environmental indicators of food web dynamics reliable: Exploring the kittiwake–temperature relationship. (April 2017) - Eerkes-Medrano, Dafne; Fryer, Robert J.; Cook, Kathryn B.; Wright, Peter J.
Abstract: This study examined the inter-relationships between kittiwake breeding success and sandeel abundance, Calanus copepods, chlorophyll and temperature. The validity of past proxies of sandeel prey ( Calanus and temperature) suggested in the literature was also examined. Winter temperature was not found to be a reliable indicator of the abundance of sandeel or lower trophic levels, although the present study did support past evidence for a dependence of kittiwake breeding success on local sandeel abundance as, with the exception of two years, there was a linear relationship with log age-0 sandeel abundance. The abundance of sandeel was positively linked to the dates of predicted peak egg abundance in C. finmarchicus and C. helgolandicus . This supported earlier evidence that the match with prey timing is important to sandeel recruitment. Neither Calanus species was associated with temperature in the February to March period nor in the April–May period, which may explain the lack of a temperature effect that propagates through the trophic levels. Consequently, although kittiwake breeding success appears to show some sensitivity and specificity to changes in their prey, this responsiveness was not found to extend to the lowest trophic level ( Calanus abundance) or to temperature. As such kittiwake breeding success was not a reliable indicator of climate-driven changes in the local food web.